Steel designers' manual - Davison, Buick; Owens, Graham W.; Steel Construction Institute (Great Britain) (Chichester, West Sussex, UK ; Hoboken, N.J. : Wiley-Blackwell, 2012)
"This classic manual on structural steelwork design was first published in 1955, since when it has sold many tens of thousands of copies worldwide. For the seventh edition all chapters have been comprehensively reviewed, revised to ensure they reflect current approaches and best practice, and brought in to compliance with EN 1993: Design of Steel Structures. The Steel Designers' Manual continues to provide, in one volume, the essential knowledge for the design of conventional steelwork. Key Features: Fully revised to comply with the new EUROCODE standards Packed full of tables, analytical design information and worked examples Contributors number leading academics, consulting engineers and fabricators 'A must for anyone involved in steel design' - Journal of Constructional Steel Research"--
Machine generated contents note: Introduction; The Eurocodes.Part1: Design Synthesis.Single storey buildings.Multi-storey buildings.Industrial applications.Residential applications.Other structural steel applications.Part 2: Steel Technology.Applied metallurgy of steel.Fatigue.Sustainability.Part 3: Design Theory.Analysis.Applicable dynamics.Part 4: Element design.Local Buckling and cross section classification.Tension Members.Columns & Struts.Beams.Plate Girders.Membrane with Compression & Moments.Trusses.Composite Deck Slabs.Composite Beams.Composite Columns.Part 5: Connection Design.Bolts.Welds.Design of connections.Foundations and Holding-Down Bolt Systems.Part 6: Other Elements.Bearing and Joints.Steel Piles.Floors.Part 7: Construction.Tolerances.Fabrication.Erection.Fire protection and fire engineering.Corrosion and corrosion prevention.Appendix.Index.
0
0
Keywords: MCE; TECHNOLOGY & ENGINEERING / Structural / bisacsh